Hidden Rice Diversity in the Guianas - Van Andel, Tinde; Veltman, Margaretha A.; Bertin, Alice; Maat, Harro; Polime, Thomas; Hille Ris Lambers, Derk; Tjoe Awie, Jerry; De Boer, Hugo; Manzanilla, Vincent (Frontiers in Plant Science, 2019)
Traditional crop varieties are an important source of genetic diversity for crop adaptation and modern breeding. Landraces of Asian (Oryza sativa) and African (Oryza glaberrima) rice have been well studied on the continents where they were domesticated. However, their history of cultivation in northern South America is poorly understood. Here we reveal the rice diversity that is maintained by Maroons, descendants of enslaved Africans who fled to the interior forests of the Guianas ca. 300 years ago. We interviewed subsistence farmers who practice shifting cultivation along the Maroni and Lawa rivers that form the natural border between French Guiana and Suriname, and used ethnobotanical and morphological methods to identify around 50 varieties, of which 15 were previously undocumented. The genetic origin of these varieties was explored using the Angiosperms353 universal probe set. Despite the large distances between sites and relative inaccessibility of the area, phenotypic and genetic diversity did not display any geographic structure, which is consistent with knowledge of seed exchange among members of the same ethnolinguistic group. Although improved US cultivars were introduced in Maroon villages in the 1940s, these have not displaced the traditional landraces, which are cherished for their taste and nutritious qualities and for their importance in Maroon spiritual life. The unique agricultural and ritual practices of Maroons confirm their role as custodians of rice diversity, a role that is currently under threat from external pressures and encroaching globalization. We expect that the rice diversity uncovered in this study represents only a fraction of the total diversity in the Guianas and may constitute a large untapped resource that holds promise for future rice improvement. Further efforts to inventory and preserve these landraces will help to protect a precious cultural heritage and local food security.